Management of soft tissue injury in the open tibia fractures - Patel, Pragnesh; P. Gandhi, Vimal (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2019)
Background and Aim: Development of newer techniques and concepts of limb salvaging such as debridement, vascular reconstruction, soft tissue reconstruction and the use of microsurgical techniques has revolutionised the treatment of open fractures. Although, not all problems that confronted trauma surgeons in the past have been completely resolved; modern methods of open fracture management, skeletal fixation and soft tissue and bone reconstructions have dramatically improved the limb salvage. Materials and Methods: The present study was a prospective study of type III B open tibia fractures treated by skeletal stabilisation and soft tissue coverage in 60 patients. Soft tissue coverage was obtained by means of SSG in 16 patients, by fasciocutananeous flap in 26 patients and by muscle flap with SSG in 18 patients. Results: In this study sound bony union was obtained in 54 out of 60 cases with soft tissue coverage in 46 cases on primary basis and in 14 patients after secondary procedures. In cases with fasciocutaneous flap who had undergone external fixator had non-union. In the present study it was observed excellent results in 49 patients, good in 10 patients and poor in 1patient based on the scoring system in which parameters like soft tissue coverage, bone union/non-union. Conclusion: Timely meticulous wound management and early soft tissue cover leads to early sound bone healing and early restoration of the function of the limb. In type III open fractures internal fixation can be contemplated when presentation is early with minimal contamination; comminution and adequate soft tissue coverage can be obtained on acute basis.